Supply chain management in the digital era: Innovations, challenges, and future directions - Rizky Surya Andhayani Nasution; Tatian Sartika Marbun; Iskandar Muda (Institute of Accounting Research and Novation (IARN), 2025)
This study looks at how supply chain management (SCM) has changed in the digital age by examining important breakthroughs, organizational difficulties, and potential future development paths. Results show that supply chain transparency, coordination, and operational efficiency are greatly improved by the use of Smart Supply Chain Management (SSCM), which is backed by cutting-edge technologies like IoT, big data analytics, blockchain, and cloud computing. The influence of SSCM on responsiveness and transparency is reinforced by supply chain coordination and mapping, which are essential mediators. Organizations still have to deal with a number of significant issues, such as system integration, data security threats, technological readiness, and limitations in digital competences. These obstacles emphasize the necessity of capacity building and all-encompassing digital transformation methods. All things considered, digitalization strengthens organizational competitiveness and resilience while also enhancing supply chain performance and real-time visibility. Future research directions stressing optimal digital integration, dynamic capability development, and the investigation of autonomous and sustainable supply chain ecosystems are highlighted in the study's conclusion.